TEACHING GRAMMAR FOR BASIC LEVEL AT POKER ENGLISH COURSE KAMPUNG INGGRIS: CHALLENGES, FACTORS AND SOLUTIONS - fatqu dewi (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2026)
This study aims to analyze the challenges teachers face in teaching basic grammar, the factors which contribute to these challenges, and the solutions implemented to overcome them. Descriptive qualitative research is utilized in this research. Data were collected through interviews, observations, and documentation. To ensure validity, data triangulation was employed to compare findings from these sources. The findings reveal several challenges, such as uneven grammar understanding among students, reluctance, drowsiness, and tardiness. These issues are influenced by diverse student backgrounds, unfamiliar terminologies, and poor sleeping habits. Based on the findings, the study highlights some implications for teaching practices. Teachers provide additional learning support outside of class hours, regularly motivate students through encouragement, and implement an energetic teaching style to sustain engagement in learning. After finding and analyzing the data of this study, it can be concluded that the teachers faced challenges in teaching basic grammar. These challenges were overcome through different solutions which helped and ensured the continued success of grammar instruction.